Correlates of diabetic polyneuropathy of the elderly in Sub-Saharan Africa - (:unkn) unknown (My University, 2020)
Background: Diabetic polyneuropathy is associated with significant physical disability among older adults. However, their frequency and correlates are not well known in the older adults in Sub-Saharan-Africa. The objectives were to evaluate the hospital-based prevalence of diabetic polyneuropathy and identify its correlates in older adults.Methods: Over a period of 5 months, a cross-sectional survey was carried out at Douala Laquintinie Hospital (DLH), a main reference hospital in Douala, the economic capital of Cameroon. Participants in our study group comprised all patients with type 2 diabetes, whatever the reason for their reporting to the hospital. Diabetic Polyneuropathy was defined according to a Diabetic Neuropathy Examination score > 3/16.Results: A total of 159 older adults with diabetes were examined during this recruitment period, among whom 106 (66.7%) were women. The mean age was 68.3 ± 6.5 years. Diabetes median duration was 108 months. For all patients assessed using the Diabetic Neuropathy Examination score, polyneuropathy was reported in 31.4%; among them, polyneuropathy proved symptomatic in 78% of them. Correlates of polyneuropathy were glycated hemoglobin (p = 0.049), HIV infection (p = 0.031) and albuminuria (p< 0.001), even after adjustment for age, gender and duration of diabetes.Conclusion: A third of older adults with diabetes who visited our hospital were diagnosed with prevalent diabetes-related polyneuropathy. It shows that early detection is required through routine screening and regular follow-up examinations in order to reduce the risk of disability and improve the quality of life in elderly diabetics.
Keywords: African Research